Characteristic features of professional and legal training of a teacherengineer - Kovalenko, D. (Problems of Engineer-Pedagogical Education, 2018)
The article considers the specificity of engineering and pedagogical training as a whole system, its components being aimed at ensuring the professional`s ability to carry out their professional duties adequately. The directions of professional training of a future teacher-engineer according to specific features of their professional activity (pedagogical, as well as engineering and industrial) have been characterized. The essence of legal training with the definition of contradictions that exist in specific fields of industry has been revealed. The aspect of the legal training importance for a teacher-engineer needed to perform engineering and industrial functions has been outlined. The levels of a specialist`s legal training in accordance with the specifics of professional activity have been characterized. An important point that has been clarified is that the legal training of a teacherengineer is a professional and legal level. The content of the legal aspect and, accordingly, the peculiarities of professional and legal training of a teacher-engineer, considering their pedagogical, as well as engineering and industrial professional functions, have been revealed.